(untitled) (Malaysian Management Journal, 2022)
Bank size is one of the vital internal determinants of banking performance, although scholars hold contradictory views on bank size and its influence on performance. The aim is to examine the effect of bank size on quoted deposit money banks (DMBs) in the region of sub-Saharan Africa (SSA). The sample, collected over a period of nine years (2011-2019) included fifty listed commercial banks drawn from across the six sub-Saharan African countries, namely Nigeria, Ghana, South Africa, Zambia, Kenya, and Tanzania. The data were analyzed using a two-step system generalized method of moment (GMM). The finding revealed a significant and negative association between bank size and its financial performance. However, the smaller banks performed better when compared to their larger counterparts in the region. These findings seem to suggest that banks keep their capital level on the high side and minimize the rate of their non-performing loans in order to achieve more excellent banking performance within the region.